2007
DOI: 10.1038/sj.ki.5001885
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin administration facilitates fluid removal during hemodialysis

Abstract: Inadequate secretion of vasopressin during fluid removal by hemodialysis may contribute to the cardiovascular instability that complicates this therapy and administration of exogenous hormone, by supporting arterial pressure, may facilitate volume removal. To test this, we measured plasma vasopressin in patients with end-stage renal disease (ESRD) during hemodialysis and found that despite significant fluid removal, plasma vasopressin concentration did not increase. We further found that ESRD did not alter the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 37 publications
2
35
1
Order By: Relevance
“…As seen in Table 2, there was no difference in serum sodium concentrations between the two groups. Previous studies demonstrate that neither hemodialysis nor ultrafiltration prevents a proportionate increase in AVP concentrations during AVP infusion (19). This suggests that AVP concentration is not affected by hemodialysis and ultrafiltration, so AVP removal cannot explain the results found in this study.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…As seen in Table 2, there was no difference in serum sodium concentrations between the two groups. Previous studies demonstrate that neither hemodialysis nor ultrafiltration prevents a proportionate increase in AVP concentrations during AVP infusion (19). This suggests that AVP concentration is not affected by hemodialysis and ultrafiltration, so AVP removal cannot explain the results found in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…Intravenous vasopressin, as recently shown in non-IDH patients (19), and perhaps intranasal vasopressin administration, may improve hemodynamic stability in an otherwise difficult to treat population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another studies reported that heart rate control is initiated and coordinated by pacemaker cells; sympathetic stimulation is associated with release of nor adrenaline , which binds to be adrenergic receptors, whereas parasympathetic stimulation is mediated by acetylcholine release, which binds to M2 muscarinergic receptors [14]. In uremia patients, increased plasma and tissue levels of catecholamine and resistance to their physiologic effect were reported by several authors [15,16,17].Clinical and laboratory evidence suggests that both B-adrenoreceptor and muscarinergic receptor -mediated responses are attenuated in the uremia state [18,19].…”
Section: Discussionmentioning
confidence: 99%